Do Schumpeterian Waves of Creative Destruction Lead to Higher Productivity? Panel Data Evidence from Poland - Frederic Warzynski (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
We look at the detfirminants and consequences of job reallocation in the 22 2-digit sectors of the manufacturing industry in Poland over the period 1993 - 1997. Import competition and competitive market structure (weak concentration) are found to lead to more reallocation. Moreover, more reallocation seems to be associated with more productive industries in some specifications. This confirms implications from neo-Schumpetarian growth models: one channel through which competition might positively affect growth is through the reallocation of scarce resources from declining firms to rising ones.
Keywords: F16; J24; J6; O3; P3; 330; Schumpetarian growth; job flows; competition; trade; Wirtschaftswachstum; Produktivität; Polen; Schumpeterismus